Preputial Grafts: The Forgotten Donor Site. Issue 6 (December 2018) - Ehrlichman, Richard J.; Driscoll, Daniel N.; Cornejo, Kristine; Upton, Joseph
Abstract : Background: The prepuce is an excellent donor site for skin grafts with minimal donor site morbidity. Full-thickness grafts are often required for correction of congenital syndactyly and in burn contractures. Methods: Preputial skin was used for grafting in 18 children: 5 with burn contractures and 13 with congenital syndactyly. Results: Excellent graft take was achieved with appropriate postoperative care. Postoperatively, there were occasional milia (42%) and hyperpigmentation. These grafts were noted to have superior mobility and elasticity. There was no donor site morbidity. Conclusions: Preputial skin is accessible, easy to harvest, and hairless and has minimal donor site morbidity. It is especially well suited for the hands and fingers when elasticity of the graft is beneficial.